Piston rings up to 200 mm diameter for reciprocating internal combustion engines. Designs, dimensions and designations for singlepiece rings. Rectangular compression rings. Specification for rectangular rings Part 7.1.1, (1st May 1992) - British Standards Institution,
No abstract available